PIN2 Polarity Establishment in Arabidopsis in the Absence of an Intact Cytoskeleton - Glanc, Matouš; Fendrych, Matyáš; Friml, Jiří (Biomolecules, 2019)
Cell polarity is crucial for the coordinated development of all multicellular organisms. In plants, this is exemplified by the PIN-FORMED (PIN) efflux carriers of the phytohormone auxin: The polar subcellular localization of the PINs is instructive to the directional intercellular auxin transport, and thus to a plethora of auxin-regulated growth and developmental processes. Despite its importance, the regulation of PIN polar subcellular localization remains poorly understood. Here, we have employed advanced live-cell imaging techniques to study the roles of microtubules and actin microfilaments in the establishment of apical polar localization of PIN2 in the epidermis of the Arabidopsis root meristem. We report that apical PIN2 polarity requires neither intact actin microfilaments nor microtubules, suggesting that the primary spatial cue for polar PIN distribution is likely independent of cytoskeleton-guided endomembrane trafficking.
Keywords: PIN auxin efflux carriers; Arabidopsis; transport proteinů; proteiny huseníčku; intracelulární prostor; actin; cytoskelet; microtubules; cytoskeleton; Arabidopsis Proteins; live-cell imaging; cell polarity; Cytoskeleton; Intracellular Space; Protein Transport; polarity establishment